Immunogenicity and safety of the quadrivalent human papillomavirus vaccine in Chinese females aged 9 to 26 years: A phase 3, open-label, immunobridging study. Issue 4 (22nd January 2021) - Huang, Zhuhang; He, Jianfeng; Su, Jiali; Ou, Zhiqiang; Liu, Guixiu; Fu, Rong; Shou, Qiong; Zheng, Minghuan; Group, Thomas; Luxembourg, Alain; Liao, Xueyan; Zhang, Jikai
Highlights: We assessed qHPV vaccine immunogenicity/safety in Chinese females aged 9–26 years (83/85 ). The qHPV vaccine elicited robust anti-HPV6/11/16/18 responses in Chinese females (82/85 ). Non-inferior immunogenicity was observed in younger versus older Chinese females (82/85) . The qHPV vaccine was generally well tolerated in Chinese females aged 9–26 years (82/85) . Abstract: Background: The quadrivalent human papillomavirus (qHPV; HPV6/11/16/18) vaccine was approved for use in Chinese women aged 20–45 years in 2017. This Phase 3, open-label study (NCT03493542) aimed to assess immunogenicity and safety of the qHPV vaccine in Chinese girls aged 9–19 years versus Chinese young women aged 20–26 years; we report results from Day 1 through Month 7. The study will continue through Month 60 to assess antibody persistence in Chinese girls aged 9–19 years. Methods: Participants aged 9–26 years received three doses of the qHPV vaccine (Day 1, Month 2, Month 6). Geometric mean titers (GMTs) and seroconversion percentages for anti-HPV6/11/16/18 antibodies were determined by competitive Luminex immunoassay (cLIA) in serum samples obtained on Day 1 and at Month 7. Injection-site adverse events (AEs) and systemic AEs within 30 days post-vaccination, and serious AEs (SAEs) occurring at any time during the study, were recorded. Results: In total, 766 participants (383 aged 9–19 years; 383 aged 20–26 years) were enrolled and received ≥1 vaccine dose. All participants in the per-protocol immunogenicity population of both age groups seroconverted to each of the vaccine HPV types at Month 7. Anti-HPV6/11/16/18 antibody GMTs at Month 7 in participants aged 9–19 years were non-inferior to those in participants aged 20–26 years. Injection-site AEs and systemic AEs were reported by 36.6% and 49.3% of 9–19-year-olds, and 40.7% and 54.8% of 20–26-year-olds, respectively. There were no vaccine-related SAEs. No participants discontinued the vaccine due to an AE and no deaths were reported. Conclusion: Antibody responses induced by the 3-dose qHPV vaccination regimen in Chinese girls aged 9–19 years were non-inferior to those in Chinese young women aged 20–26 years. The vaccine was generally well tolerated in the study population. ClinicalTrials.gov Identifier: NCT03493542.